Teacher-assisted peer assessment and self-efficacy in writing: A quasi-experiment among Ethiopian undergraduate EFL students - Alemayehu Leta Abo; Hailu Wubshet Degefu; Berhan Demeke Abeba (Social Sciences and Humanities Open)
This study examines the impact of teacher-assisted peer assessment on EFL learners' writing self-efficacy. A non-equivalent pre-test and post-test control group quasi-experimental design was employed to answer the research questions. The participants of the study were 60 second-year economics students from two intact groups who enrolled in basic writing skills course. The two groups were assigned into the experimental group (N = 30) and the control group (N = 30) using lottery method without randomization. The students in the experimental group were given paragraph writing tasks and were exposed to teacher-assisted peer assessment for eight weeks. The students in the control group were given the same writing tasks and were exposed only to teacher assessment practice. Pre-and post-writing self-efficacy questionnaires were used to gather data to examine whether there was significant difference between the two groups. The quantitative data were analyzed using descriptive statistics (mean and standard deviation) and inferential statistics (independent sample t-test, paired sample t-test and One-Way Analysis of Covariance (ANCOVA). Semi-structured interviews were also conducted with experimental group students to complement the quantitative data. The results indicated that teacher-assisted peer assessment significantly enhanced students' writing self-efficacy, but with moderate effect size (partial ŋ2 = .092). The interview results also revealed that exposing students to teacher-assisted peer assessment was motivating and contributed to enhancing students' writing self-efficacy. Therefore, it is recommended that teacher-assisted peer assessment should be integrated into the writing curriculum and utilized in writing classes to enhance students’ writing self-efficacy.